A granular Discrete Element Method for arbitrary convex particle shapes: Method and packing generation. (2nd November 2018) - Seelen, L.J.H.; Padding, J.T.; Kuipers, J.A.M.
Graphical abstract: Highlights: A new DEM method is introduced to simulate any convex particle shape. The method uses a new contact point detection scheme. Mechanical stability is achieved, even for tall towers of particles. Packings of cuboids, cylinders and ellipsoids are investigated in detail. More complex sand and woodchip particles are also investigated. Abstract: A novel granular discrete element method (DEM) is introduced to simulate mixtures of particles of any convex shape. To quickly identify pairs of particles in contact, the method first uses a broad-phase and a narrow-phase contact detection strategy. After this, a contact resolution phase finds the contact normal and penetration depth. A new algorithm is introduced to effectively locate the contact point in the geometric center of flat faces in partial contact. This is important for a correct evaluation of the torque on each particle, leading to a much higher stability of stacks of particles than with previous algorithms. The granular DEM is used to generate random packings in a cylindrical vessel. The simulated shapes include non-spherical particles with different aspect ratio cuboids, cylinders and ellipsoids. More complex polyhedral shapes representing sand and woodchip particles are also used. The latter particles all have a unique shape and size, resembling real granular particle packings. All packings are analyzed extensively by investigating positional and orientational ordering.